Achieving the sustainable development goals in agriculture using nano fertilizer in cereal based system. (2022) - Chitkara, Mansi; Tewari, Anurag; Pranav; Kumar, Aashish; Dhillon, Gulshan
Abstract: In recent times, the application of engineered nanoparticles has increased in the agricultural sector due to their use as nano-pesticides, nano-fertilizer, nano-sensors etc. A field trial of Nano fertilizer in Pusa Basmati 1509 was laid down in the present study to promote sustainable agriculture in rice production to reduce the consumption of urea in the region. Magnetite (Fe3 O4 ) was used as a nanofertilizer for the present study, synthesized using co-precipitation technique and characterized by X-ray Diffraction (XRD) to confirm the phase and purity of the material. Influence of Magnetite was observed on yield and quality attributes of Pusa Basmati 1509 in comparison to control as well as various sources of nitrogen. Nanofertilizer in combination with a reduced quantity of urea was beneficial for the yield enhancement (15.64 Qtls/Acre) and quality (64.9 % Brown Head Rice) improvement of Pusa Basmati 1509. The use of nanofertilizer in isolation resulted in higher yield (13.72 Qtls/Acre) compared to control (9.2 Qtls/Acre). The application of Farmyard manure and poultry manure too resulted in higher farm yield (12.3Qtls/Acre and 11.76 Qtls/Acre respectively) in comparison to control (9.2 Qtls/Acre). This showed that the combination of urea and nanofertilizer had a synergistic effect.Thus, use of nanofertilizer reduced urea consumption in Pusa Basmati 1509, enhancing its yield and improving brown head rice recovery.